2022
DOI: 10.3389/fcell.2022.855178
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin and Resveratrol Modulate the Gliotic and Pro-Angiogenic Response in Müller Glial Cells Under Hypoxia

Abstract: Hypoxia and hypoxia-reoxygenation are frequently developed through the course of many retinal diseases of different etiologies. Müller glial cells (MGCs), together with microglia and astrocytes, participate firstly in response to the injury and later in the repair of tissue damage. New pharmacological strategies tend to modulate MGCs ability to induce angiogenesis and gliosis in order to accelerate the recovery stage. In this article, we investigated the variation in autophagy flux under hypoxia during 4 h, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…Previous studies have already described an increase in cell death in cultured rat Mu ¨ller cell line (rMC-1) after 24 h treatment with cobalt chloride [34]. Similarly, a loss of cell viability in MIO-M1 cells treated with cobalt chloride in different concentrations, including the same one used in our study (400 μM), has been documented [35,36].…”
Section: Plos Onesupporting
confidence: 82%
“…Previous studies have already described an increase in cell death in cultured rat Mu ¨ller cell line (rMC-1) after 24 h treatment with cobalt chloride [34]. Similarly, a loss of cell viability in MIO-M1 cells treated with cobalt chloride in different concentrations, including the same one used in our study (400 μM), has been documented [35,36].…”
Section: Plos Onesupporting
confidence: 82%
“…In fact, the autophagy status within Muller cells is likely to be relevant to trans-synaptically modulating retinal homeostasis. It is shown that Muller cells, depending on their autophagy status, may induce neoangiogenesis and inflammation, which occurs during retinal degeneration [124]. Even Muller cells' viability is promoted by autophagy activation, which impedes Muller cells' apoptosis retinal degeneration [125].…”
Section: Downstream Of Outer Retinamentioning
confidence: 99%
“… 63 , 64 Interestingly, despite the finding of a hypoxia-mediated reduction of Iba1 + cell accumulation in ndufs4 − / − mouse brain lesions by Mootha and colleagues 29 and our finding of reduced retinal gliosis, other models have demonstrated that hypoxia itself may stimulate a pro-inflammatory microglial response and the activation of astrocytes and Müller glia. 33 , 61 , 65 67 These discrepancies might reflect different effects of short-term (hours or days) versus long-term hypoxia (months, as in our study) or of intermittent rather than continuous exposure to hypoxia.…”
Section: Discussionmentioning
confidence: 54%